Publicistica eminesciană reinterpretată de Ion Dur. Recenzie de carte - Mihai POSADA (Eon, 2025)
The volume M. Eminescu. private thinker and journalist with a “scientific method”, published under the number 110 in the «Eminesciana» series by Junimea Publishing House in Iași in 2024, is structured by Professor Ion Dur into two parts: “Elements of Private Thought” and “Journalist with a 'Scientific Method.” Asserting that “one arrives at Eminescu but does not remain there!”, the author’s call necessarily directs readers to the study of Eminescu’s manuscripts. For Ion Dur, the coffer containing Eminescu’s manuscripts is a “holy ark of Romanian identity.” Essential remains the approach of the “context of composition” of Eminescu’s texts and the “context of reception” for any hermeneutic attempt. The author’s conclusions—that Mihai Eminescu is a “function of Romanian culture” and at the same time the first “publicist who writes in a newspaper as if he were writing literature”—thus lead to “a different Eminescu”. “Being our first great political journalist, unsurpassed to this day by those who adopted his style of discourse,” Eminescu blends elements of sociology and political philosophy into his journalistic writing.